The Influence of Work Culture and Achievement Motivation on the Quality of Learning at Public Vocational High Schools in Serang City - Endang Sri Mulyani; Syadeli Hanafi; Isti Rusdiyani (International Journal of Community Engagement Payungi, 2025)
This study was driven by three critical issues: (1) the weak implementation of work culture among vocational high school (SMK) teachers, despite their role as student role models; (2) the need to enhance teachers’ achievement motivation to continuously improve competencies and adapt to the rapid advancement of industrial technology; and (3) the suboptimal learning quality in public SMKs in Serang City, as evidenced by the low employment absorption of graduates. The purpose of this research was to examine the influence of work culture and achievement motivation—both individually and jointly—on the quality of learning. A descriptive quantitative research design was employed, utilizing multiple linear regression analysis with SPSS Statistics version 23. The research instrument, tested for validity and reliability on 30 teachers, produced 60 valid items across three variables and was subsequently distributed to 86 teachers from public SMKs in Serang City. The partial test (t-test) results showed that work culture (p = 0.002) and achievement motivation (p = 0.000) had significant individual effects on the quality of learning. Furthermore, the simultaneous test (F-test) yielded an F value of 84.179 with a significance level of 0.000, confirming that both factors had a strong and significant combined influence on learning quality. These findings underscore the importance of fostering a positive work culture and strengthening teachers’ achievement motivation to enhance the educational outcomes in vocational high schools.